DOING THINGS WITH COMPUTERS. - Bailey, Jason (Art in America, 2020)
The article examines how software has made generative methods accessible to artists, from the 1990 to 2019. Topics discussed include impact of aspects of lives driven by computation and algorithms on art; use of the computer as an art-making tool in the late 1960; and demand for great digital content far exceeding the number of people with the skills to produce it.